Construction of Evaluation Index System of Office Sitting Comfort Based on Ergonomics. (31st August 2022) - Hu, Jiadian; Shi, Shoudong; Zheng, Jiaqing; Fang, Zhiyuan
Abstract : People who sit incorrectly can have musculoskeletal disorders like cervical spondylosis and lumbar vertebra disease, but without the guidance of a health care professional, it is difficult for people to evaluate their posture and adopt a more appropriate posture. Therefore, to solve this problem, we established a multilevel sitting posture evaluation system by analyzing the parameters such as joint angle, joint torque, joint force, and muscle force. Use the analytic hierarchy process and entropy comprehensive weighting method to weight evaluation indicators. According to their evaluation standards, each parameter is given weight after quantization and normalization. Firstly, take several sitting postures that often appear in office work as examples and use the lower back analysis and joint and static pressure analysis tools in JACK software for simulation analysis. Then, the weights of various parameters such as joints and muscles of the human body were calculated using the hierarchy analysis and entropy weight method, and the quantitative evaluation system of office sitting comfort was constructed. We recruited 50 subjects for an office simulation experiment to verify the feasibility of the evaluation index. Finally, we classified the sitting posture and selected those commonly used in life for evaluation. The proposed sitting posture evaluation system can objectively and comprehensively reflect the quality of sitting posture and guide people to adopt what kind of sitting posture.